Achieving enhanced ML or RTP performance: alkyl substituent effect on the fine-tuning of molecular packing. (12th November 2020) - Yu, Yun; Fan, Yuanyuan; Wang, Can; Wei, Yao; Liao, Qiuyan; Li, Qianqian; Li, Zhen
Abstract : By changing the substituted alkyl chain of PIth–C derivatives to well regulate the stacking angles of molecular dimers, and considering the efficient intermolecular interactions, their ML/RTP performance could be well tuned. Abstract : Mechanoluminescence (ML) and room temperature phosphorescence (RTP) have generally been considered to be highly related to the molecular packing in the solid state; accordingly, the regulation of packing through molecular design is particularly important. Unlike most previous research, flexible alkyl substituents instead of aromatic substituents were utilized to fine-tune the molecular packing in this work. Really, just simply modifying different alkyl substituents on the aromatic core, the PIth–C derivatives exhibited regular changes in molecular packing accompanied by tunable ML/RTP properties. Among them, PIth–C3 and PIth–C4 displayed largely enhanced ML intensities, while PIth–C5 and PIth–C6 had much better RTP performance. The enhancement of ML and RTP could be ascribed to the effective suppression of nonradiation under different conditions, through distinct crystal packing modes and strong intermolecular interactions. This alkyl substituent effect reveals an effective strategy for the molecular design of ML and RTP luminogens, with deep understanding of the structure–packing–property relationship.